Role for Linezolid in drug sensitive tuberculosis - S. Ramesh Kumar; G. Narendran; C. Padmapriyadarsini (Elsevier, 2024)
Tuberculosis (TB) continues to be a global challenge. Reducing the duration of TB treatment for drug-sensitive TB (DSTB) has direct and distinct advantages. We ventured into the aspect of utilizing linezolid as a pivotal drug in shortening therapy in DSTB. Linezolid has gained prominence as it is faring well in resistant TB management. Only a few studies use the strategy of Linezolid in DS-TB but it seems a lucrative approach, the bactericidal effects have been reported favourably in the studies. There have been concerns about the potential adverse drug effects of Linezolid reported but clinical trials have demonstrated safety and tolerability when administered for shorter periods. If the safety and efficacy of giving Linezolid for a shorter period along with standard drugs for DSTB is established it could lead to newer avenues using Linezolid for shortening the duration of treatment for DSTB as an alternative to treat DSTB.